واقع تطبيق الإستراتيجية التنافسية في المؤسسة الإقتصادية - كمون حاج بلقاسم, شريقي عبد الله (My University, 2022)
This study aims to shed light on the importance and impact of general competitive strategies and the extent of their application in the economic institution, especially in light of the openness of the global market and the continuous development of external variables. A private sector is free to make decisions that enhance its competitiveness, and a public sector is subject to a number of considerations (legal, political, social,...) mainly represented by the Algerian state , which had a direct impact in enhancing the company’s competitiveness at times and in obstructing it at other times In addition to the internal factors that affected the development of Mobilis since the beginning of the new millennium, which made it more difficult to define its strategic options.
دراسة حالة شركة موبيليس
Keywords: Competitive strategy, Mobilis, differentiation strategy, strategic diagnosis.